Efektivitas Program Rehabilitasi Sosial pada Dinas Sosial dalam Penanganan Gelandangan dan Pengemis di Kota Jambi - Dimas Martua Panggabean; Riri Maria Fatriani; Fajar Alan Syahrier; Dimas Subekti (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2026)
The phenomenon of homeless individuals and beggars (gepeng) in Jambi City remains a significant and ongoing social issue, indicating that efforts to address poverty and urban social vulnerability have not yet been fully effective. Although the local government, through the Jambi City Social Affairs Office, has implemented a Social Rehabilitation Program aimed at restoring beneficiaries’ social functioning through outreach, social assessment, social guidance, skills training, and family reunification, the presence of gepeng in public spaces continues to fluctuate from 2022 to 2024. This study analyzes the effectiveness of the program’s implementation, particularly the social guidance component, using a qualitative case study approach. Data were collected through in-depth interviews, field observation, and documentation review, and analyzed using George C. Edward III’s policy implementation theory, which emphasizes communication, resources, disposition, and bureaucratic structure. The findings show that the program has been carried out procedurally and humanely; however, its effectiveness remains limited due to insufficient numbers of social workers, weak and unsustained economic empowerment support, and inadequate post-rehabilitation monitoring. As a result, some beneficiaries return to the streets after completing the program. Therefore, strengthening inter-agency communication, increasing resource capacity, integrating sustainable economic empowerment initiatives, and improving consistent monitoring systems are essential steps to achieve long-term and more sustainable reductions in homelessness in Jambi.